Exosomal PD-L1: New Insights Into Tumor Immune Escape Mechanisms and Therapeutic Strategies - Zhou, Kaijian; Guo, Shu; Li, Fei; Sun, Qiang; Liang, Guoxin (Frontiers in Cell and Developmental Biology, 2020)
As a classical immune checkpoint molecule, PD-L1 on the surface of tumor cells plays a pivotal role in tumor immunosuppression, primarily by inhibiting the antitumor activities of T cells by binding to its receptor PD-1. PD-1/PD-L1 inhibitors have demonstrated unprecedented promise in treating various human cancers with impressive efficacy. However, a significant portion of cancer patients remains less responsive. Therefore, a better understanding of PD-L1-mediated immune escape is imperative. PD-L1 can be expressed on the surface of tumor cells, but it is also found to exist in extracellular forms, such as on exosomes. Recent studies have revealed the importance of exosomal PD-L1 (ExoPD-L1). As an alternative to membrane-bound PD-L1, ExoPD-L1 produced by tumor cells also plays an important regulatory role in the antitumor immune response. We review the recent remarkable findings on the biological functions of ExoPD-L1, including the inhibition of lymphocyte activities, migration to PD-L1-negative tumor cells and immune cells, induction of both local and systemic immunosuppression, and promotion of tumor growth. We also discuss the potential implications of ExoPD-L1 as a predictor for disease progression and treatment response, sensitive methods for detection of circulating ExoPD-L1, and the novel therapeutic strategies combining the inhibition of exosome biogenesis with PD-L1 blockade in the clinic.